Fractal Characteristics of Pore Structure of Longmaxi Shales with Different Burial Depths in Southern Sichuan and Its Geological Significance - Manping Yang; Yanyan Pan; Hongye Feng; Qiang Yan; Yanjun Lu; Wanxin Wang; Yu Qi; Hongjian Zhu (Fractal and Fractional)
Burial depth can significantly impact the pore structure characteristics of shale. The Lower Silurian Longmaxi Shale in the Weiyuan block of the Sichuan Basin is a marine formation that we studied for deep shale gas exploration. We used two groups of Longmaxi samples, outcrop shale and middle-deep shale, to investigate the pore structure fractal features at varying burial depths using a combination of mineralogy, organic geochemistry, scanning electron microscopy (SEM), and low-temperature gas (CO2, N2) adsorption. The V-S fractal model was used to determine the fractal dimension (Dc) of micropores, and the FHH fractal model was used to determine the fractal dimension (DN) of mesopores. The findings indicate that the pore morphology of organic matter becomes irregular and more broken as the burial depth increases, as does the content and maturity of organic matter. The pore size of organic matter gradually decreases, the SSA (BET, DR) and PV (BJH, DA) of shale pores increase, the pore structure becomes more complex, and the average shale pore size decreases. According to this study, the organic matter content and its maturity show an increasing trend as burial depth increases. Meanwhile, the organic matter’s pore morphology tends to be irregular, and fracture rates rise, which causes the organic matter’s pore size to gradually decrease. In addition, the SSA (comprising the values assessed by BET and DR techniques) and PV (evaluated by BJH and DA methods) of shale pores grew, suggesting that the pore structure became more complex. Correspondingly, the average pore size of the shale decreased. The fractal dimensions of the micropores (DC), mesoporous surface (DN1), and mesoporous structure (DN2) of outcrop shale are 2.6728~2.7245, 2.5612~2.5838, and 2.7911~2.8042, respectively. The mean values are 2.6987, 2.5725, and 2.7977, respectively. The DC, DN1, and DN2 of middle-deep shale are 2.6221~2.7510, 2.6085~2.6390, and 2.8140~2.8357, respectively, and the mean values are 2.7050, 2.6243, and 2.8277, respectively. As the fractal dimension grows, the shale’s pore structure becomes more intricate, and the heterogeneity increases as the buried depth increases. The fractal dimension has a positive association with the pore structure parameters (SSA, PV), TOC, and Ro and a negative association with the mineral component (quartz, feldspar, clay mineral) contents. Minerals like quartz, feldspar, and clay will slow down the expansion of pores, but when SSA and PV increase, the pore heterogeneity will be greater and the pore structure more complex.